A taxonomic revision of the genera of the subtribe Dracophilinae (Aizoaceae: Ruschioideae) - Mannheimer, Coleen Anne (Rhodes University, Faculty of Science, Botany Department, 2006)
Namibia, Juttadinteria and Dracophilus, the three genera belonging to the subtribe Dracophilinae Schwantes (Aizoaceae: Ruschioideae) were revised. Macro-morphology, leaf anatomy and micromorphology of leaf epidermides, pollen, tapetal orbicules and seed were studied in order to test taxon limits, to determine relationships between taxa, and to improve knowledge of their characteristics as well as the taxonomy of the subtribe. The investigation was based on herbarium specimens, field observations and cultivated, living plants. Phenetic cluster analyses were used to confirm species while intergeneric and interspecific relationships of the taxa so indicated were later tested by means of a phylogenetic analysis. The existence of the three genera was provisionally upheld by this study although phylogenetic analysis showed Namibia nested as a strongly supported monophyletic group within a poorly supported luttadinteria. Further work is needed to clarify whether Namibia should be sunk into Juttadinteria. The latest treatments of Juttadinteria and Dracophilus by Hartmann (2001) were supprted. However, in contrast to her latest treatment of Namibia, N. pomonae was sunk into N. cinerea and N. ponderosa was reinstated and typified. Juttadinteria was found to be a poorly resolved genus with many intergrading and overlapping characters, possible due to recent speciation. Possible subspecific groups within J. deserticola and J. simpsonii were indicated by the phenetic study but further work is needed before any formal infraspecific taxonomic rank can be assigned to them. Detailed descriptions of the nine elucidated species and the three genera as well as new keys for their identification are provided in order to facilitate further work in this group. Distribution maps are provided for the genera and species, and the subtribe. Variation of character states within the subtribe, distribution area, ecology and biology are discussed.
Keywords: Aizoaceae; Plants -- Classification; Cladistic analysis